Urinary Incontinence during Sleep Associated with Extended Release Form of Bupropion HCI - Izci, Filiz; Iris Koc, Merve; Bilici, Rabia; Yalcin, Murat; Bestepe, Engin Emrem (Case Reports in Psychiatry, 2015)
Bupropion hydrochloride (HCI) is an antidepressant that acts as a norepinephrine and dopamine reuptake inhibitor and has three different dosage forms including immediate release (IR), sustained release (SR), and extended release (ER). Despite its relatively safe side effect profile bupropion may cause several side effects. Here, we aimed to report a case with major depression using extended release form of bupropion hydrochloride who was presented with urinary incontinence during sleep, an uncommon side effect of bupropion.